Impact of in vitro costimulation with TLR2, TLR4 and TLR9 agonists and HIV-1 on antigen-presenting cell activation (2015)
HIV-1 infects several immune cells including dendritic cells (DCs) and monocytes, which contributes in both to dissemination of HIV-1 infection and induction of antiviral immunity.